Parental Somatic Mosaicism Uncovers Inheritance of an Apparently De Novo GFAP Mutation - Grossi, Alice; Morelli, Federico; Di Duca, Marco; Caroli, Francesco; Moroni, Isabella; Tonduti, Davide; Bachetti, Tiziana; Ceccherini, Isabella (Frontiers in Genetics, 2021)
Alexander disease is a leukodystrophy caused by heterozygous mutations of the GFAP gene. Recurrence in siblings from healthy parents provides a confirmation to the transmission of variants through germinal mosaicism. Using DNA isolated from peripheral blood, Next Generation Sequencing (NGS) of the GFAP locus was performed with deep coverage (≥500X) in 11 probands and their parents (trios) with probands heterozygous for apparently de novo GFAP mutations. Indeed, one parent had somatic mosaicism, estimated in the range 8.9%-16%, for the mutant allele transmitted to the affected sibling. Parental germline mosaicism deserves attention as it is critical in assessing the risk of recurrence in families with Alexander disease.